Effects of an online program including mindfulness, exercise therapy and patient education compared to online exercise therapy and patient education for people with Patellofemoral Pain: protocol for a randomized clinical trial - Priore, Liliam Barbuglio Del [UNESP]; Perez, Vitoria Ozores [UNESP]; Briani, Ronaldo Valdir [UNESP]; Farinelli, Lucca Andre Liporoni Bego [UNESP]; da Silva, Júlia de Cássia Pinto [UNESP]; Martins, Odisséia Marli Gimenes; Lopes, Fábio Arruda; Amorim, Anita Barros; Pappas, Evangelos; de Azevedo, Fábio Mícolis [UNESP] (Springer Nature, 2023)
Background: Patellofemoral pain (PFP) is a common knee disorder that causes persistent pain, lower self-reported function and quality of life. People with PFP also present with altered psychological factors, which are associated with higher levels of pain and dysfunction. Mindfulness-based interventions (MBI) generally consist of meditative practices developed to provide a holistic approach to chronic conditions. However, the effects of MBI on clinical and psychological outcomes for people with PFP remains understudied. Methods: This assessor-blinded, parallel, two-arm randomized clinical trial aims to investigate the effects of adding an 8-week online MBI program to exercise therapy and patient education on clinical and psychological factors for people with PFP. We also aim to investigate whether psychological factors mediate changes in pain and function. Sixty-two participants with PFP will be recruited and randomized into one of two treatment groups (Mindfulness or Control group). Both groups will receive an 8-week intervention involving exercise therapy and education delivered through an online platform. The Mindfulness group will additionally receive a MBI component including formal and informal practices. Outcomes will be assessed online at baseline, intervention endpoint (follow-up 1) and 12 months after intervention completion (follow-up 2). Comparisons between groups will be performed at all time points with linear mixed models. A mediation analysis will be performed using a 3-variable framework. Discussion: Exercise therapy and patient education are considered the “best management” options for PFP. However, unsatisfactory long-term prognosis remains an issue. It is known that people with PFP present with altered psychological factors, which should be considered during the evaluation and treatment of people with PFP. Adding a MBI to the current best treatment for PFP may improve short and long-term effects by addressing the underlying psychological factors. Trial registration: Registro Brasileiro de Ensaios Clínicos (ReBEC) RBR-4yhbqwk, registered in April 6, 2021.
Keywords: Anterior knee pain; Education; Exercise therapy; Mindfulness; Psychological factors